2009
DOI: 10.1016/j.ygyno.2009.03.028
|View full text |Cite
|
Sign up to set email alerts
|

p53 autoantibodies, cytokine levels and ovarian carcinogenesis

Abstract: Objective To address the hypothesis that type II ovarian carcinoma, mutation of p53 and plasma levels of particular cytokines are associated with the generation of p53-specific serum autoantibody (AAb) responses inpatients. Methods Levels of CA125, 17 cytokines and AAbs to tumor-associated antigens includingp53 were measured in plasma of 130 gynecologic tumor patients and 84 healthy controls. TP53exons 4–9 were sequenced in tumor specimens. Results p53 AAbs are associated with high grade, but not low grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 35 publications
(52 reference statements)
4
54
0
Order By: Relevance
“…Some studies claim that higher levels are associated with advanced disease. 30,31 In our study population, we showed that both the lowest as well as the highest serum levels of CCL-2 were independently associated with a poor prognosis. A possible explanation might lay in the findings that CCL-2 can act Table 4.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Some studies claim that higher levels are associated with advanced disease. 30,31 In our study population, we showed that both the lowest as well as the highest serum levels of CCL-2 were independently associated with a poor prognosis. A possible explanation might lay in the findings that CCL-2 can act Table 4.…”
Section: Discussionmentioning
confidence: 59%
“…Acts immune suppressive, increases proteolytic activity of cells, adhesion and directly stimulates angiogenesis 44 Inhibits the function of CD8 C cytotoxic T cells and Th1 cells Inhibits the development of M1 macrophages from monocytes and plays an indispensable role in tumor development and progression 45 TGFß1 mRNA expression is an indicator of tumor sensitivity to standard therapy that it can identify biologically aggressive and highly malignant tumors and can predict the prognosis of patients with ovarian cancer 46 Serum level of TGF-b1 has no diagnostic and prognostic role and is associated with sensitivity to standard chemotherapy in ovarian cancer patients 47 CCL-2 /MCP-1 One of the key chemokines that regulate migration and infiltration of monocytes, memory T cells, NKC and DC to sites of inflammation. Has both tumor growth-promoting as growth-inhibiting influences 48,49 Chemotherapy (paclitaxel-carboplatin) can upregulate CCL-2 expression 50 Elevated CCL-2 expression by ovarian cancer cells is reported to be associated both with a better chemotherapy (paclitaxelcisplatin) responses 51 as with chemotherapy resistance 52 CCL-2 levels in serum of ovarian cancer patients compared to healthy controls are both described to be lower 28,29 as higher 30,31 Higher levels are associated with advanced disease 30,31 …”
Section: Tgf-bmentioning
confidence: 99%
“…p53 mutation are high with type II tumors, thus p53 autoantibodies are associated with high grade tumors. Tsai-Turton et al [47] demonstrated that serum p53 autoantibodies levels were significantly higher in patients with type II ovarian carcinoma as compared to those of healthy women (P < .001). p53 autoantibodies level are found to be significantly higher in patients with advanced-stage (III/IV) type II carcinoma as compared to patients with early-stage (I/II) type II carcinoma (P < .001).…”
Section: A P53mentioning
confidence: 97%
“…p53 autoantibodies level are found to be significantly higher in patients with advanced-stage (III/IV) type II carcinoma as compared to patients with early-stage (I/II) type II carcinoma (P < .001). Up to 80% ovarian tumors exhibit mutated p53, however investigations are carried out on why only 20% to 40% of these tumors exhibit autoantibodies to p53 [47].…”
Section: A P53mentioning
confidence: 99%
“…In ovarian cancer these autoantibodies are associated with high grade ovarian cancer which is characterised by predominantly Type II tumours [28]. Serous papillary adenocarcinoma is a Type II ovarian cancer and in our cohort of late stage serous papillary adenocarcinoma we measured an incidence of 25% of patients with p53…”
Section: Accepted M Manuscriptmentioning
confidence: 99%